The Relationship between Polymorphisms in the Vitamin D Receptor Gene and Bone Mineral Density in Postmenopausal Women. (9th January 2014) - Moran, Jose M.; Rodriguez-Velasco, Francisco J.; Roncero-Martin, Raul; Rey-Sanchez, Purificación; Martinez, Mariana; Pedrera-Zamorano, Juan D.
Abstract : The objective of this study was to identify, through a systematic review of the literature, Vitamin D receptor gene ( VDR ) polymorphisms related to osteoporosis and their effects on bone mineral density (BMD). The articles dated between January 2000 and December 2011 in the Scielo and PubMed databases were reviewed. A total of 23 articles that studied the association between the BsmI, ApaI, FokI, and TaqI polymorphisms and bone mineral density in postmenopausal women were selected. We found systematic studies/meta-analysis (level E-I) and case-control/cohort (level E-IV) studies. No definite conclusions can be made regarding the association of BsmI, ApaI, FokI, and TaqI polymorphisms with BMD among postmenopausal women. Larger and more rigorous analytical studies with consideration of gene-gene/environment interactions are needed to further dissect the mechanisms by which VDR alleles influence BMD.